ANALYSIS OF THE EFFECTIVENESS OF THE FAMILY HOPE PROGRAM ON STUNTING IN CHILDREN AGED 24-36 MONTHS IN KUTA BARO SUB-DISTRICT, ACEH BESAR DISTRICT - Kala, Pasyamei Rembune; Jannah, Rauzahtun (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2023)
Stunting is a nutritional problem facing Indonesia, especially Aceh. This is important because it concerns the quality of Aceh's human resources in the future. Efforts to prevent and reduce stunting cannot be done only by the health sector, but by involving cross-sectors and of course from within the family itself.  One of the health problems facing the community, especially the poor, is nutritional problems that can cause stunting in children. Children who come from poor families are certainly at great risk of stunting, because they have the potential to experience long-term malnutrition. One of the government programs that has been implemented in order to reduce the problem of stunting is the Family Hope Program (PKH).   This study aims to determine how the effectiveness of the Family Hope Program on stunting in children aged 24-36 months in Kuta Baro District, Aceh Besar Regency. This research uses qualitative research methods with a descriptive analysis approach.   Data collection techniques through observation, interviews and documentation. The results of this study indicate that the implementation of PKH in preventing stunting includes preventive efforts including encouraging changes in KPM behavior through agreed commitments, with the assistance funds provided by PKH can help KPM in fulfilling nutrition for family members. The technical implementation of PKH in Kuta Baro District is in accordance with government regulations in efforts to eradicate poverty and prevent stunting. The amount of PKH assistance funds is based on the criteria met by the Beneficiary Family (KPM).